2021
DOI: 10.3389/fmed.2021.653634
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Hyperkalemia in Patients With Chronic Kidney Disease: An Old Problem With News Options

Abstract: Hyperkalemia is one of the main electrolyte disorders in patients with chronic kidney disease (CKD). The prevalence of hyperkalemia increases as the Glomerular Filtration Rate (GFR) declines. Although chronic hyperkalemia is not a medical emergency, it can have negative consequences for the adequate cardio-renal management in the medium and long term. Hyperkalemia is common in patients on renin-angiotensin-aldosterone system inhibitors (RAASi) or Mineralocorticoid Receptor Antagonists (MRAs) and can affect tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 85 publications
(80 reference statements)
2
13
0
1
Order By: Relevance
“…High serum uric acid levels are associated with high risk for advanced CKD and CKD progression [51,52], the prevalence of hyperuricemia was 30.9% in advanced CKD; advanced CKD had a 2.4-fold higher OR if a patient had hyperuricemia and 2.4-fold higher if a patient was on allopurinol; similar findings have been reported in other studies [23,53]. Hyperkalemia is common in patients with chronic CKD and its prevalence increases as the eGFR declines [54,55], approximately 8.8% patients with advanced CKD were found to have hyperkalemia; hyperkalemia had a 5.4-fold increased association with advanced CKD; similar findings have been reported in other studies [24,25]. Studies have shown that the incidence of cardiovascular events increases with worsening kidney function [56,57]; 22.7% patients with advanced CKD reported angina with a 2.5 times increased risk in advanced CKD, similar to other studies [56,58].…”
Section: Plos Onesupporting
confidence: 79%
“…High serum uric acid levels are associated with high risk for advanced CKD and CKD progression [51,52], the prevalence of hyperuricemia was 30.9% in advanced CKD; advanced CKD had a 2.4-fold higher OR if a patient had hyperuricemia and 2.4-fold higher if a patient was on allopurinol; similar findings have been reported in other studies [23,53]. Hyperkalemia is common in patients with chronic CKD and its prevalence increases as the eGFR declines [54,55], approximately 8.8% patients with advanced CKD were found to have hyperkalemia; hyperkalemia had a 5.4-fold increased association with advanced CKD; similar findings have been reported in other studies [24,25]. Studies have shown that the incidence of cardiovascular events increases with worsening kidney function [56,57]; 22.7% patients with advanced CKD reported angina with a 2.5 times increased risk in advanced CKD, similar to other studies [56,58].…”
Section: Plos Onesupporting
confidence: 79%
“…Hyperkalaemia was significantly associated with CKD progression on univariate analysis but this significance was lost on multivariate analysis. Studies have reported that high serum potassium levels are common in patients with chronic CKD and it is associated with decreased renal function and CKD progression; its prevalence increases as the eGFR declines (62, 63). Metabolic acidosis was not significantly associated with CKD progression in this study; studies from other settings reported that patients with low serum bicarbonate levels had higher rates of CKD progression and an accelerated reduction in eGFR with poor outcomes (64, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of SPS and CPS in treating chronic hyperkalemia may be limited due to lack of evidence and increasing reports of serious gastrointestinal side effects. 7 , 16 In a number of RCTs, patiromer has shown excellent efficacy and safety in treating hyperkalemia in CKD patients. 4 , 7 , 10 , 16 Future research is necessary to prospectively evaluate the comparative efficacy and safety of current treatment options in British Columbia, including SPS/CPS with newer treatment choices, for example, patiromer and sodium zirconium cyclosilicate.…”
Section: Discussionmentioning
confidence: 99%
“…However, its efficacy in treating chronic hyperkalemia among CKD patients is also not well established. 7 …”
Section: Introductionmentioning
confidence: 99%